FRI0220 Aortic involvement at onset impacts long term outcome in giant cell arteritis: A 12 years follow-up study. (23rd January 2014) - Espitia, O.; Néel, A.; Leux, C.; Connault, J.; Ponge, T.; Dupas, B.; Barrier, J.-H.; Hamidou, M.; Agard, C.
Abstract : Background: Aortitis is a potential life-threatening complication of GCA. Up to 30-50% of cases of GCA may have clinical or radiological signs of aortitis (1). Images of aortic involvement may be non symptomatic and their real outcome remain elusive. Objectives: This study was conducted to describe the long-term outcome of patients with or without suspicion of aortitis at the time of diagnosis of GCA. Methods: Twenty-two patients with newly diagnosed biopsy-proven GCA were explored in 1999 using aortic computed tomodensitometry (CT). Ten patients (group 1) had aortic inflammatory thickenings ≥3mm (n=7) and/or aneurism (n=3), whereas 12 patients had no aortitis (group 2). A retrospective study of these 2 groups was conducted in 2011. We contacted and questioned the patients, their family and general practitioner, and analysed each medical file. The following items were investigated: demographic data, cardio-vascular risk factors, total and cardio-vascular mortality, cardio-vascular events, GCA relapses, corticosteroids regimen. Satistics were made using R development Core Team (2009) software. Results: This study included 17 women and 5 men (mean age at diagnosis = 73.7±7.2 y). Inflammatory parameters and cardio-vascular risk factors were similar in group 1 and 2. The mean follow-up was 94.8 months. Twelve years after diagnosis of GCA, the total mortality was 50% without differences between group 1 (7/10) and group 2 (5/12). However, the 12y cardio-vascular mortality was statistically higher in patients with initial suspicion of aortitis (50%), than in patients without (0%, p=0.029, Log rank test). In group 1, the causes of deaths of cardiovascular origin were: rupture of abdominal aortic aneurism (n=1), thoracic aortic dissection (n=1), stroke (n=1), heart failure (n=1), peripheral arterial disease (n=1). Twelve cardio-vascular events occured in 7/10 patients of group 1 whereas only 5 occured in 4/12 patients of group 2. Stroke were statistically more frequent in group 1 (40% vs 0% in group 2, p=0.03). Recurrent GCA relapses were noted in 5/10 patients of group 1, 0/12 patients of group 2 and this difference was statistically significant (p=0.01). Moreover, definitive steroid treatment discontinuation was more frequent in group 2 (n=2) than in group 1 (n=8, p<0.05). Conclusions: Despite the limitations due to its retrospective character and its small number of patients, our study suggests that GCA clinical course may differ according to initial CT signs of aortic involvement. CT suspicion of aortitis may lead to aortic fatal events and aortic thickenings deserve to be monitored. Initial aortic CT involvements seem to sign a particular form of GCA, with higher rate of cardio-vascular events and mortality, and with frequent relapses requiring longer steroids treatment. References: Agard C, Barrier JH, Dupas B, et al. Arthritis Rheum 2008;59(5):670-6 Disclosure of Interest: None Declared